Milk thistle may induce apoptosis in development of carbontetrachloride-induced liver DNA damage in rats - Aslan, Abdullah; Can, Muhammed Ismail; Kuloglu, Tuncay; Baspinar, Serpil (Mattioli 1885, 2016)
The leaf and flower extracts of Slybum marianum [Milk thistle (MT)] have been used for liver, gall bladder and spleen disorders for centuries. 28 male Wistar albino (n = 28, 8 weeks old) rats used in the study. The rats divided into 4 groups according to their live weights. The groups were: (i) Negative Control (NC): Normal water consuming group to which no CCl4 and MT is administered; (ii) Positive Control (PC): Normal water consuming group to which no CCl4 is administered but MT is administered; (iii) CCl4 Group: Normal water consuming and group to which CCl4 is administered (2 ml/kg live weight, ip); CCl4 + MT group: CCl4 and MT administered group (2 ml/kg live weight, ip). Tissue apoptotic index was examined via TUNEL method. MDA determination in plasma tissue was carried out using a spectrophotometer. As a Results, MDA amount decreased in the CCl4 + MT group (3,65 +/- 0,15 nmol/ml) in comparison to CCl4 group (4,25 +/- 0,21 nmol/ml) whereas it was observed in the CCl4 + MT group (12,62 +/- 0,91 %) that the apoptotic index (TUNEL results) decreases in comparison with the CCl4 group (22,62 +/- 0,91 %) thus approaching normal values. These results show that MT plant has a protective effect on liver.
Keywords: CCl4; DNA damage; liver damage; Milk thistle; TUNEL